Factorial Sum!

1 1 ! + 2 2 ! + 3 3 ! + + 25 25 ! = ? \large 1 \cdot 1! + 2\cdot 2! + 3\cdot 3! + \cdots + 25\cdot 25! = \, ?

26 ! + 1 26! + 1 26 ! + 25 ! + + 2 ! 26! + 25! + \cdots + 2! 30 ! 3 30! - 3 26 ! 1 26! - 1

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

11 solutions

Mohtasim Nakib
Jan 20, 2016

I am best at maths in the world. I know what 1+1 is .It is 2

Sophia Park - 1 year, 10 months ago
Neha Gupta
May 15, 2015

Can be written as (2-1) 1! + (3-1) 2! + ...... (25-1) 24! + (26-1) 25! Further, it simplifies to 2!-1!+3!-2!+4!-3!+.....25!-24!+26!-25! which gives us 26!-1 as the correct answer.

can u elaborate neha gupta

Bharat Naik - 6 years ago

Log in to reply

Create a difference form In RHS rightmost last term 26!-25!+25!-24!.....2!-1!=and

Mikhil Gupta - 5 years ago

That's gorgeous, Neha! Thank you. Like a telescoping series.

Eli Lieberman - 4 years, 9 months ago

How did you make the first analysis of (2-1) as the correct simplification?

Erik Kaiser - 4 years, 1 month ago

Neha in which class u are

Riya Verma - 3 years, 4 months ago
Tijmen Veltman
May 1, 2015

We can prove by induction that, more generally:

k = 1 n k k ! = ( n + 1 ) ! 1 \sum_{k=1}^n k\cdot k! = (n+1)!-1

for all positive integers n n .

For n = 1 n=1 we get 1 = 2 ! 1 1=2!-1 , which is correct.

Suppose now that the statement holds for certain n N n\in\mathbb{N} . Then we have:

k = 1 n + 1 k k ! = ( n + 1 ) ! 1 + ( n + 1 ) ( n + 1 ) ! = ( n + 2 ) ( n + 1 ) ! 1 = ( n + 2 ) ! 1. \sum_{k=1}^{n+1} k\cdot k! = (n+1)!-1+(n+1)(n+1)! = (n+2)(n+1)!-1 = (n+2)!-1.

Hence the statement holds for all natural n n . Plugging in n = 25 n=25 , we obtain:

1 1 ! + 2 2 ! + + 25 25 ! = 26 ! 1 . 1\cdot 1!+2\cdot 2!+\ldots+25\cdot 25!=\boxed{26!-1}.

Moderator note:

Good. There's another way to obtain this. Hint: k = k + 1 1 k = k+1 - 1 .

Can you interpret this number? If we arrange all possible permutation of alphabets in ascending order (from A A smallest to Z Z largest), then what position would { Z , Y , X , W , V , , C , B , A } \{Z,Y,X,W,V,\ldots, C,B,A \} be?

A nice alternate solution is to write k = k + 1 1 , k=k+1-1, so k k ! = ( k + 1 1 ) k ! = ( k + 1 ) k ! k ! = ( k + 1 ) ! k ! . k\cdot k! = (k+1-1)\cdot k! = (k+1)\cdot k! - k! = (k+1)! - k!.

Then, the terms of the sum cancel out, and we are left with ( 25 + 1 ) ! 1 ! = 26 ! 1. (25+1)! - 1! = 26!-1. This approach is known as a Telescoping Series Sum .

Eli Ross Staff - 5 years, 8 months ago

for Tijmen Veltman solution, plugging n=25 gets you 27!-1

David Moore - 3 years, 11 months ago

Log in to reply

noasdnfoksadjfasdf ]

jazel libaton - 3 years, 5 months ago

Log in to reply

What's this

Riya Verma - 3 years, 4 months ago
Rishav Koirala
Jul 28, 2016

Let S = 1 1 ! + 2 2 ! + 3 3 ! + . . . 25 25 ! S=1\cdot 1!+2\cdot 2!+3\cdot 3!+...25\cdot 25! and let A = 1 ! + 2 ! + 3 ! + 4 ! + . . . 25 ! A=1!+2!+3!+4!+...25! . Then,

S + A = ( 1 1 ! + 1 ! ) + ( 2 2 ! + 2 ! ) + ( 3 3 ! + 3 ! ) + . . . ( 25 25 ! + 25 ! ) S+A=(1\cdot 1!+1!) +(2\cdot 2!+2!) +(3\cdot 3!+3!) +...(25\cdot 25!+25!) Or, S + A = 2 ! + 3 ! + 4 ! + . . . 26 ! = A 1 + 26 ! S+A= 2!+3!+4!+...26! = A-1 + 26!

This gives,

S + A = 26 ! + A 1 S+A=26!+A-1

Or, S = 26 ! 1 S = 26!-1 .

Gokul Jagannadh
May 17, 2015

the LHS can be written as (1-0).1!+(3-1).2!+(4-1).3!+.......+(26-1).25! on simplification we will get 1!+3!-2!+4!-3!+5!-4!...........+26!-25! = 1!-2!+3!-3!+4!-4!+5!-5!+..........+25!-25!+26! =26!-2+1 = 26!-1

Shay Pecker
Jul 13, 2016

k*k!=(k+1)!-k! so all of the terms cancels out except of -1! and 26!, Which gives us 26!-1!

Apoorv Pandey
May 11, 2015

nth term = n.n! In place of first n put n+1-1 and multiply. nth term becomes n+1! - n!.

Juan Cruz Roldán
Oct 27, 2020

Can be proven with a strong induction: ( n + 1 ) ! 1 + n + 1 ( n + 1 ) ! = ( n + 1 ) ! ( n + 1 + 1 ) 1 = ( n + 2 ) ! 1 (n+1)!-1+n+1(n+1)! = (n+1)!(n+1+1)-1 = (n+2)!-1

Antonije Mirkovic
Aug 15, 2020

I did something totally different from all the other comments here.

what i did is that i found out what the answer of 1 1!+2 2!+3 3!+4 4!+5*5! would be.

i basically then solved 1+4+18+36+600, and got 719.

i then noticed that my answer is just 1 number away from 6!, and thus, my answer = 6!-1.

I applied this for the full question, and immediately saw that the correct answer is 26!-1.

I have been using this technique for several problems here, and it always works. reduce the problem to smaller numbers which are easier to deal with, calculate them, and then predict what the answer is going to be. For some problems you will need more calculations to predict the answer even better.

may not be the best "mathematical way", but this technique could be useful when stuck at questions in competitive maths.

Anand Singh
May 29, 2017

let 1·1!+2·2!+3·3!+.........+25·25! = x

Add 1!+2!+3!+.......+25! on both sides

we get,

  2·1!+3·2!+4·3!+...........+26·25! = x + 1!+2!+3!+..........+25!

  2!  + 3! + 4! + .........+25! + 26! = x + 1! + 2! + 3! +.......... +25!

  26! = x + 1!

Thus, x=26! - 1! = 26! -1

or,

1·1!+2·2!+3·3!+.........+25·25! = x = 26! - 1

Suyash Baranwal
May 15, 2015

It's a formula. The proof is simple. Replace n by n+1-1 in n.n! to get n+1!-n! Then simply add the terms to get n+1!-1.Therefore, the answer 26!-1

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...